Preparation of TA-cloned positive control for diagnostic PCR detection of phytoplasma associated with Cassava phytoplasma disease - Alviar, Karen B.; Claire S. Ramos (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2020)
Cassava is one of the main foods in the country with more than 15 million Filipinos consuming this crop as staple or supplemental food. It is also a raw material used for feeds, alcohol and other industrial products. However, the Philippine cassava industry faces an emerging disease called Cassava Phytoplasma Disease (CPD). CPD is caused by a bacteria-like organism called phytoplasma. Here, we wanted to confirm phytoplasma infection in cassava showing witches’ broom symptoms typical of CPD. We carried out molecular analysis using polymerase chain reaction (PCR), cloning, restriction enzyme digestion and sequencing methods to identify a cassava phytoplasma strain from an infected cassava plant showing symptoms of CPD. Plant DNA was extracted and used as a template in PCR reaction using universal primers amplifying the 16S rRNA region of phytoplasma. A nested PCR using primer pair R16mF2/R16mR1 in the first amplification followed by R16F2n/R16R2n in the second amplification was performed. PCR products were purified and transformed in a TA cloning vector. Following restriction enzyme digestion for insert verification, plasmid DNA about 1.5 kb in size was sequenced. Blast n search revealed homology with a phytoplasma strain causing sugarcane grassy shoot disease. Plasmid DNA with established sequence identity based on homology to 16S rRNA phytoplasma will serve as our positive control template for future PCR diagnostics of plant or insect samples associated with cassava phytoplasma disease.